Time to fight: targeting the circadian clock molecular machinery in cancer therapy. Issue 5 (May 2021) - Astone, Matteo; Santoro, Massimo M.
Highlights: Circadian rhythmicity and the expression of core clock genes are altered in cancer settings. Cancer molecular pathways and biological features can disrupt the circadian clock. A dysregulated circadian clock favors tumor initiation and progression. Genetic and pharmacological manipulations of the clock can counteract tumor growth. Abstract : The circadian clock regulates a wide range of molecular pathways and biological processes. The expression of clock genes is often altered in cancer, fostering tumor initiation and progression. Inhibition and activation of core circadian clock genes, as well as treatments that restore circadian rhythmicity, have been successful in counteracting tumor growth in different experimental models. Here, we provide an up-to-date overview of studies that show the therapeutic effects of targeting the clock molecular machinery in cancer, both genetically and pharmacologically. We also highlight future areas for progress that offer a promising path towards innovative anticancer strategies. Substantial limitations in the current understanding of the complex interplay between the circadian clock and cancer in vivo need to be addressed in order to allow clock-targeting therapies in cancer. Teaser: Genetic and pharmacological targeting of circadian clock machinery, as well as treatments that restore circadian rhythmicity, show the potential to counteract tumor growth in vitro and in preclinical models.